2020
DOI: 10.4149/neo_2019_190414n328
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1203 is involved in hepatocellular carcinoma metastases and indicates a poor prognosis

X Li2,
et al.

Abstract: Non-coding RNAs, especially miRNAs, have been shown to be important regulators in multiple human diseases, including malignant tumors, congenital disease, and autoimmune disease. In this study, we screened the metastasis-associated miRNAs in hepatocellular carcinoma (HCC). Based on the miRNA microarray screening, miR-1203 was confirmed to be the most significant miRNA and was also highly associated with HCC metastases. Bioinformatics prediction indicated direct binding of miR-1203 in SOCS3, which was also conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The average number of differential miRNAs per cancer was 7 ± 1.08, with hsa-miR-125a-3p, hsa-miR-887-3p, and hsa-miR-1203 being differentially expressed in all 13 cancer types. Studies reported that these three miR-NAs are associated with cancerogenesis and progression in multiple cancers [22][23][24]. This result suggests common alterations in serum miRNAs in different cancer types.…”
Section: Low Cancer Specificity Of 5-mirpairs For Gliomamentioning
confidence: 85%
“…The average number of differential miRNAs per cancer was 7 ± 1.08, with hsa-miR-125a-3p, hsa-miR-887-3p, and hsa-miR-1203 being differentially expressed in all 13 cancer types. Studies reported that these three miR-NAs are associated with cancerogenesis and progression in multiple cancers [22][23][24]. This result suggests common alterations in serum miRNAs in different cancer types.…”
Section: Low Cancer Specificity Of 5-mirpairs For Gliomamentioning
confidence: 85%
“… 66 In a similar study, miR-1203 suppresses SOCS3 in HCC by binding to its 3′-UTR region, which promotes over-phosphorylation of STAT3, increased HCC cell proliferation and invasion, hepatic fibrosis, and tumor aggressiveness. 67 Furthermore, miR-6887-5p overexpression causes suppression of signal transduction in transforming growth factor beta (TGF-β), mediated by Smad3. This leads to dysregulation of diverse cellular processes such as cell proliferation, differentiation, migration and apoptosis which promotes the development of multiple cancers such as CC, BC, ovarian cancer, and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs have been reported previously to cause various different cancers such as, HCC, prostate cancer, pancreatic cancer, and ovarian cancer. 61 , 67 , 68 , 71 Hence, it is suggested that anti-miR drugs should be developed that can target these oncomiRs and downregulate their expression, which may lead to normal expression of the SOCS3. 72 …”
Section: Discussionmentioning
confidence: 99%
“…MiR-1203 has been identified as a potential serum biomarker for prostate cancer [ 53 ] and a predictor of prognosis for hepatocellular carcinoma [ 54 ].…”
Section: Discussionmentioning
confidence: 99%